The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s00408-009-9219-6
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Positive Airway Pressure Improves Sleep Apnea Associated Fatty Liver

Abstract: Treatment of sleep apnea can improve liver enzyme abnormalities in patients with nonalcoholic fatty liver disease. However, the effect of continuous positive airway pressure therapy for sleep apnea on liver fat accumulation was not assessed. Liver biopsy is the "gold standard" for determining and quantifying liver fat accumulation; however, obtaining two separate liver biopsies is challenging. We examined, using a newly described computerized tomography method to quantify liver fat accumulation, whether treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 28 publications
2
35
2
Order By: Relevance
“…However, we have recently shown that treatment of OSA with CPAP reduces postprandial lipids after only 8 weeks [17]. In the present study, although we could not also demonstrate significant reductions in abdominal or liver fat over a similar treatment period, an uncontrolled study using CPAP that assessed liver fat over 2-3 yrs did demonstrate a reduction in liver fat [16]. Hence, it is possible that a longer treatment period may eventually also show a benefit [17,28].…”
Section: Sleep-related Disorders S Sivam Et Alcontrasting
confidence: 53%
See 1 more Smart Citation
“…However, we have recently shown that treatment of OSA with CPAP reduces postprandial lipids after only 8 weeks [17]. In the present study, although we could not also demonstrate significant reductions in abdominal or liver fat over a similar treatment period, an uncontrolled study using CPAP that assessed liver fat over 2-3 yrs did demonstrate a reduction in liver fat [16]. Hence, it is possible that a longer treatment period may eventually also show a benefit [17,28].…”
Section: Sleep-related Disorders S Sivam Et Alcontrasting
confidence: 53%
“…Markers of hypoxia have been demonstrated to be associated with elevated serum aminotransferase levels [14]. Similarly to visceral fat, however, there are contrasting results on the effect of nasal CPAP on the biochemical markers of NALFD in patients with OSA [12,15,16].…”
mentioning
confidence: 99%
“…Unravelling mechanisms mediating OSAS-associated liver injury in NAFLD would have major research and clinical implications, as current therapeutic approaches to paediatric OSAS yield disappointing results: severe OSAS persists in as many as 50% of children after adeno-tonsillectomy, especially in the presence of obesity and severe OSAS;23 CPAP therapy improves polysomnographic parameters and surrogate markers of NAFLD,28 29 but its feasibility and patient adherence in children remain an issue 10. Therefore, it is important to investigate the novel alternative or complementary strategies for the treatment of paediatric OSAS.…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-sectional studies have reported elevated levels of liver enzymes in patients with OSAS. Shpirer et al [41] demonstrated increased ALT, AST, and alakaline phosphate in adult patients with moderate to severe OSA. In a study by Gude et al [42] serum gamma glutamine transferease levels directly correlated with a degree of nocturnal hypoxemia in OSA patients.…”
Section: Discussionmentioning
confidence: 98%